Using AI to Calculate Research Payments. - Różyńska, Joanna K (American Journal of Bioethics, 2026)
This article focuses on the ethical and practical challenges of determining payment for clinical research participants and proposes the use of artificial intelligence (AI) tools to improve this process. While payment to participants is common and important for recruitment and diversity, there is no global consensus on standards or ethical guidelines, with existing frameworks like the Declaration of Helsinki offering limited guidance and the Council for International Organizations of Medical Sciences (CIOMS) providing more detailed but non-binding recommendations. The article argues that AI-powered, rule-based systems could assist investigators and ethics committees in calculating fair, equitable, and non-exploitative payments by integrating local economic data, regulatory requirements, and ethical criteria, thereby addressing current inconsistencies and complexities in payment practices across diverse research settings. This proposed AI application differs from other AI uses in clinical trial recruitment by emphasizing transparency and ethical fairness rather than cost-effectiveness.